2005
DOI: 10.1083/jcb.200509028
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative elucidation of a distinct spatial gradient-sensing mechanism in fibroblasts

Abstract: Migration of eukaryotic cells toward a chemoattractant often relies on their ability to distinguish receptor-mediated signaling at different subcellular locations, a phenomenon known as spatial sensing. A prominent example that is seen during wound healing is fibroblast migration in platelet-derived growth factor (PDGF) gradients. As in the well-characterized chemotactic cells Dictyostelium discoideum and neutrophils, signaling to the cytoskeleton via the phosphoinositide 3-kinase pathway in fibroblasts is spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
105
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(108 citation statements)
references
References 50 publications
3
105
0
Order By: Relevance
“…Our computational model suggested that slow interstitial flow can cause pericellular CXCL12 gradients of at least 1% to form around a circular cell. Such gradients are sufficient to elicit directional migration in other cell types including neutrophils (37), fibroblasts (38), and dendritic cells (39). We, in fact, see both directional cell polarization and migration in response to flow through our studies possibly indicating a role for autologous chemotaxis complementary to enhanced chemokinesis.…”
Section: Discussionmentioning
confidence: 49%
“…Our computational model suggested that slow interstitial flow can cause pericellular CXCL12 gradients of at least 1% to form around a circular cell. Such gradients are sufficient to elicit directional migration in other cell types including neutrophils (37), fibroblasts (38), and dendritic cells (39). We, in fact, see both directional cell polarization and migration in response to flow through our studies possibly indicating a role for autologous chemotaxis complementary to enhanced chemokinesis.…”
Section: Discussionmentioning
confidence: 49%
“…Several Rac GEFs are activated by phosphatidylinositol-(3-5)-triphosphate, including Vav, Tiam1, PIX, and p-REX (46). Rac activity may be sustained through feedback loops, as Rac can interact with the p85 regulatory subunit of class 1A PI3Ks in leukocytes, although possibly not in fibroblasts (26,47). Although activation of Akt downstream of PI3K is implicated in cell migration via Rac/Pak pathway, the mechanism of Akt activation is poorly understood (48)(49)(50)(51).…”
Section: Discussionmentioning
confidence: 99%
“…In fibroblasts, chemotaxis to PDGF is also characterised by polarised localisation of PtdIns(3,4,5)P 3 . However, modelling predicts that localised PtdIns(3,4,5)P 3 accumulation primarily reflects receptor occupancy and is not regulated by feedback amplification or inhibition proposed for ameboid cells (Schneider and Haugh, 2005). Indeed, migration of fibroblasts is slower than that of amoeboid cells and although driven by membrane protrusion, it also involves substantial contribution of differential adhesion (Lauffenburger and Horwitz, 1996), suggesting distinct requirements for gradient sensing.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, migration of fibroblasts is slower than that of amoeboid cells and although driven by membrane protrusion, it also involves substantial contribution of differential adhesion (Lauffenburger and Horwitz, 1996), suggesting distinct requirements for gradient sensing. Furthermore, it has been shown that robust PDGF sensing requires steeper gradients and a much narrower range of absolute chemoattractant concentration (Schneider and Haugh, 2005).…”
Section: Introductionmentioning
confidence: 99%